IMPLIKASI KOMPENSASI DAN STRES KERJA TERHADAP TURN OVER KARYAWAN UNIT KEPERAWATAN RUMAH SAKIT X SUKABUMI: Manajemen sumberdaya manusia - Reka Ardian Purnama & Savitri Larasati (Ekonomedia, 2020)
The purpose of this study was to determine the effect of compensation and work stress on employee turnover in nursing unit of hospital X. The design in this study uses descriptive research methods and associative methods with a quantitative approach. The population in this study were employees in nursing unit of hospital X with a population of 226 employees so that using the Yamane formula was finally obtained, the sample used was 144 respondents. . To test the analysis of research instruments used validity test, reliability test and classical assumption test, then for statistical analysis tests and analysis of relationships and effects used Pearson product moment correlation, coefficient of determination, multiple linear regression and to test the hypothesis used the T test and F test.Based on the results of the T test research that has been carried out, it can be seen that partially indirect compensation has a positive effect on employee turnover at nursing unit of hospital X. The results of the T test show partially. The results also show that work stress has a positive effect on employee turnover at nursing unit of hospital X. The results of the study also said that simultaneously through the results of the F test, it showed that compensation and work stress simultaneously had a positive effect on employee turnover in the employee turnover at nursing unit of hospital X. The amount of contribution (Determination Coefficient Value) of the effect of compensation and work stress on employee turnover at nursing unit of hospital X, seen from the results of R Squra is 20.0%, while the remaining 80% is influenced by other variables not studied. Such as work discipline, motivation, work experience, work environment, workload, and organizational culture.